From current status to optimization of HCV treatment: Recommendations from an expert panel. Issue 9 (September 2016) - ,; Aghemo, Alessio; Alberti, Alfredo; Andreone, Pietro; Andreoni, Massimo; Bonora, Stefano; Brunetto, Maurizia Rossana; Bruno, Savino; Caporaso, Nicola; Chirianni, Antonio; Ciancio, Alessia; Degasperi, Elisabetta; et al.
Abstract: Chronic hepatitis C virus (HCV) infection is a major public health problem at a global level, causing an enormous burden of hepatic and extra-hepatic morbidity and mortality. Treatment of chronic HCV (CHC) has been revolutionized in the last few years by the introduction of highly effective and well tolerated direct acting antiviral agents (DAAs) able to achieve >90% rates of sustained virological response (SVR) in many groups of patients, including those previously excluded from interferon-based regimens. For such reason interferon-free regimens are now the treatments of choice for all patients. Successful anti-HCV treatment can stop liver disease progression and can solve the HCV-related extra hepatic manifestations, eventually reducing both liver-related and overall mortality. Together with the rapidly accumulating data about the evolution of treatment landscape, different guidelines from national and international Liver Scientific Societies have been published until today. However, these recommendations may not be applied worldwide as, due to high treatment costs, most of them identify as priority groups only patients with advanced liver disease. Moreover some types of patients pose clinical management problems for which even the guidelines do not always provide useful answers. With the aim of treatment optimization by filling some of the gaps of the current guidelines and addressing the remaining unmet needs in practice, a group of Italian experts, experienced on treatment of HCV infection, met in Stresa in February 2016. The summary of all the considerations arising from this two-day meeting and the final statements are reported in this position paper.